2020
DOI: 10.1093/jamia/ocaa125
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing outpatient problem list completeness and duplications in the electronic health record

Abstract: Abstract Objective The study sought to characterize rates of problem list completeness and duplications in common chronic diseases and to identify any relationships that they may have with respect to disease type, demographics, and disease severity. Materials and Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…This can be burdensome and stresses the importance of widespread availability of testing. Evidence also suggests that patients with more significant or severe comorbidities are likely to have more complete health records [ 26 , 27 ]. This effect may have overrepresented patients with more severe chronic conditions in the untreated group based on the application of mAb eligibility criteria for inclusion in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This can be burdensome and stresses the importance of widespread availability of testing. Evidence also suggests that patients with more significant or severe comorbidities are likely to have more complete health records [ 26 , 27 ]. This effect may have overrepresented patients with more severe chronic conditions in the untreated group based on the application of mAb eligibility criteria for inclusion in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown EHR problem list incompleteness rates between 10% and 60% for an individual health system. 18 , 19 , 23 For the 4 measures that included diagnoses as part of the measure calculation (ie, diabetes and hypertension measures), over 24% of measure calculations change when HIE data are included. Because data sharing through an HIE closes a portion of incomplete diagnoses before quality calculation, the magnitude of measure discrepancies observed in this research generally align with incompleteness expectations from other research.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, attempts to characterize endometriosis through data collection designs relying solely on EHR problem lists might yield incomplete or biased results, findings supported by previous studies conducting in other conditions. 14 16 90 From a clinical standpoint, pain variability has been demonstrated to be predictive of treatment response and disease outcomes. 79 91 For example, a study 79 reported that higher within-person pain variability at baseline in a randomized controlled trial for a fibromyalgia pain drug was predictive of placebo response and nonspecific treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of EHR problem list completeness and accuracy reports that providers struggle more with maintaining complete problem lists for patients whose diseases status are less severe and less symptomatic. 16 Accordingly, some of the patients identified in the EHR cohort might have reported additional pain-related findings, but these might have not been documented by the provider.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation